2008
DOI: 10.1063/1.2931040
|View full text |Cite
|
Sign up to set email alerts
|

Depth profile photoemission study of thermally diffused Mn/GaAs (001) interfaces

Abstract: A study of the growth of Lu 2 O 3 on Si(001) by synchrotron radiation photoemission and transmission electron microscopy Surface electronic structure in transition-metal (Cr and Mn) doped GaAs (001) studied by in situ photoemission spectroscopy Appl.We have performed a depth profile study of thermally diffused Mn/GaAs ͑001͒ interfaces using photoemission spectroscopy combined with Ar + -ion sputtering. We found that Mn ion was thermally diffused into the deep region of the GaAs substrate and completely reacted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To explain this discrepancy, we can speculate that the observed diffusion really occurred at the cleaved surface and not through the whole layer. Likewise, we must conclude that the diffusion reported between Mn and GaAs [11], where a similar band bending situation should occur, was due to ion beam related knock-in effects rather than thermal diffusion.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…To explain this discrepancy, we can speculate that the observed diffusion really occurred at the cleaved surface and not through the whole layer. Likewise, we must conclude that the diffusion reported between Mn and GaAs [11], where a similar band bending situation should occur, was due to ion beam related knock-in effects rather than thermal diffusion.…”
Section: Resultsmentioning
confidence: 88%
“…The inability of Mn to diffuse through GaAs has also been observed in experiments on (Ga, Mn)As capped with thin GaAs films, in which case the effect of post-growth annealing was eliminated for 10 ML thick capping [9]. On the other hand, crosssectional scanning tunneling microscopy (STM) images from (Ga, Mn)As/GaAs multilayer structures suggest that the Mn concentration in 60 ML thick GaAs spacers may be as high as 10-20% of the total Mn concentration in the (Ga, Mn)As after annealing treatment [10], and a depth profiling study of a Mn/GaAs interface indicated massive diffusion of Mn into GaAs [11]. These apparently contradictory pictures of the (Ga, Mn)As/Ga interface require further studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of thermodynamic stability of the Mn/GaAs(001), Mn/GaN(001), and Mn/GaP(001) thin films have shown that, with increasing annealing temperature, synthesis of Mn 2 As, MnAs, and MnP occurs and both epitaxial and polycrystalline Mn x Ga 1− x clusters are formed 12–16. The same synthesis products can be obtained via implantation of Mn ions in GaAs 17 and GaN 18, 19 substrates.…”
Section: Introductionmentioning
confidence: 95%